2023
DOI: 10.3390/plants12030624
|View full text |Cite
|
Sign up to set email alerts
|

Current Insights into m6A RNA Methylation and Its Emerging Role in Plant Circadian Clock

Abstract: N6-adenosine methylation (m6A) is a prevalent form of RNA modification found in the expressed transcripts of many eukaryotic organisms. Moreover, m6A methylation is a dynamic and reversible process that requires the functioning of various proteins and their complexes that are evolutionarily conserved between species and include methylases, demethylases, and m6A-binding proteins. Over the past decade, the m6A methylation process in plants has been extensively studied and the understanding thereof has drasticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 148 publications
0
4
0
Order By: Relevance
“…N 6methyladenosine (m 6 A) modification of circadian gene CCA1 is regulated by light-induced phase separation of CRYs, which interact with m 6 A writer complex and accelerate CCA1's degradation. This finding highlights the important role of m 6 A modification in plant circadian rhythm (Chuong et al, 2023;Wang et al, 2021). Additionally, natural variation in miR397 can affect the circadian period and flowering time in Arabidopsis, indicating the posttranscriptional role of miRNA in plant circadian regulation (Feng et al, 2020).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…N 6methyladenosine (m 6 A) modification of circadian gene CCA1 is regulated by light-induced phase separation of CRYs, which interact with m 6 A writer complex and accelerate CCA1's degradation. This finding highlights the important role of m 6 A modification in plant circadian rhythm (Chuong et al, 2023;Wang et al, 2021). Additionally, natural variation in miR397 can affect the circadian period and flowering time in Arabidopsis, indicating the posttranscriptional role of miRNA in plant circadian regulation (Feng et al, 2020).…”
Section: Introductionmentioning
confidence: 65%
“…While circadian transcription was originally believed to be the primary contributor to mRNA abundance, mounting evidence suggests that circadian post‐transcriptional regulation also plays a significant role in modulating the RNA life cycle (Torres et al., 2018). Several steps of RNA processing, including RNA alternative splicing, RNA chemical modification, and RNA export, exhibit circadian oscillation (Chuong et al., 2023; Fustin et al., 2013; McGlincy et al., 2012; Torres et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The most canonical consensus motif of the m 6 A modification site is RRACH (R = G or A; H = U, A or C) [13], which accounts for more than 90% of the m 6 A sites in wheat mR-NAs [14]. Numerous studies in plants also identified this dominant consensus motif [15][16][17]. Alternative motifs of GGAU and URUAY (Y = C or U) were also found to be enriched in plant species by epitranscriptome analysis [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, the expression levels of OsPITP-related genes were found to be greatly affected by Magnaporthe oryzae infection. In their review article, Chuong et al [ 10 ] reported that N6-adenosine methylation (m 6 A) is an evolutionarily conserved, dynamic, and reversible process across species that occurs as a complex with a variety of proteins, including methylases, demethylases, and m 6 A binding proteins. In plants, the regulatory function of the m 6 A methylation component has been shown to be involved in various elements of RNA processing, such as RNA stability, alternative polyadenylation, and miRNA regulation.…”
mentioning
confidence: 99%